Trend Research Analysis Pantang Larang (Prohibitions or Taboos) in Moral Learning in Children in Malay Society - HM, Muhammad Yusuf; Puteh, Saifullizam Bin; Marpuah, Siti (Journal Governance Society, 2024)
The Malay society emphasizes moral education through pantang larang (prohibitions or taboos), which are deeply embedded in cultural and Islamic teachings. These prohibitions act as tools to guide children’s behavior and shape their moral character, instilling values such as respect, discipline, and responsibility. This research explores the role of pantang larang in moral learning for Malay children. The study's objective is to analyze the relevance and application of pantang larang in shaping moral education and address its challenges in modern society. A literature review method was employed, drawing on scholarly articles, journals, and books that discuss cultural practices, Islamic teachings, and character development. The analysis revealed that pantang larang contributes significantly to moral education by subtly guiding children through prohibitions that align with ethical principles, such as respecting elders and avoiding harmful behaviors. It also reflects local wisdom and reinforces virtues essential for maintaining social harmony. However, the study highlights the challenge of preserving pantang larang amidst globalization and modern cultural shifts. Results suggest that integrating pantang larang into contemporary educational settings through innovative methods, such as digital storytelling, can help retain its moral lessons while engaging younger generations. The conclusion underscores that pantang larang remains a vital cultural tool for character formation, with universal moral values applicable beyond Malay society. Modernizing its teaching methods while preserving its essence can ensure that pantang larang continues to nurture ethical and culturally grounded individuals in an evolving global context.